The pronoun in ortonese : A contrastive study - Tucci, Emiliana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article we will study the pronominal system in Ortonese, which belongs to the central-southern Italo-Romance languages. The analysis we propose is contrastive: we will compare the data with the Italian to highlight their differences in terms of some morphosyntactic aspects. We will examine, the stressed and unstressed personal pronouns, emphasizing the placement of the combined pronouns with the compound tenses. Then, we will focus on the rest of the pronouns, such as demonstratives, possessives, quantifiers and indefinites, also pointing out the uses of the clitics “ci” and “ne” and the presence of the pronoun “nome”, which does not exist in Italian.